An annotated checklist of Iranian aquatic Polyphaga: Georissidae, Helophoridae, Hydrochidae, Spercheidae, Curculionidae and Erirhinidae (Insecta: Coleoptera). Issue 4 (2nd October 2018) - Darilmaz, Mustafa C.; Ostovan, Hadi; Ghahari, Hassan; Angus, Robert B.
Abstract: The checklist comprises all species of six families of Iranian aquatic Polyphaga (Coleoptera). In total, 43 species/subspecies within the families, Georissidae (one species), Helophoridae (25 species and two subspecies), Hydrochidae (three species), Spercheidae (one species), Curculionidae (nine species) and Erirhinidae (two species) are listed for the fauna of Iran. Helophorus ( Rhopalohelophorus ) nanus Sturm, 1836 (Helophoridae) is recorded for the first time from Iran. We also present two additional species lists: one with incorrect records (one species) and the other with unidentified species.